1997
DOI: 10.1002/(sici)1097-0215(19970422)74:2<171::aid-ijc5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-d1-gene amplification and expression in breast carcinoma: Relation with clinicopathologic characteristics and with retinoblastoma gene product, p53 and p21waf1 immunohistochemical expression

Abstract: Cyclin D1 is a major positive regulator of the G 1 restriction point promoting inactivation of the retinoblastoma protein (RB). The cyclin D1 gene is rearranged, amplified and/or over-expressed in several human neoplasms. In the present series of 64 human breast carcinomas, cyclin D1 amplification (4-to 8-fold) was seen in 24% of cases, and cyclin-D1 immuno-histochemical over-expression was seen in 50% of cases. Amplification and over-expression were statistically associated ; however, divergent result were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
41
0
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 12 publications
12
41
0
1
Order By: Relevance
“…Our findings largely coincide with those of Michalides et al (21), who studied 243 breast cancers and Barbareschi et al (22), who reported on 64 tumors. Like both of these groups, we found no correlation between cyclin D1 and p53 abnormalities in the whole cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings largely coincide with those of Michalides et al (21), who studied 243 breast cancers and Barbareschi et al (22), who reported on 64 tumors. Like both of these groups, we found no correlation between cyclin D1 and p53 abnormalities in the whole cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Our data support the concept that persistent elevation of intranuclear cyclin D1 occurs early in mammary neoplasia and is maintained during tumor progression (17). Like two other studies (22,23), but unlike a third one (20), we found no association between cyclin D1 status and DNA ploidy. We were not able to study the association between positive estrogen receptor status and cyclin D1 overexpression, as has been documented by a number of other investigators (6,18,21,22).…”
Section: Discussionsupporting
confidence: 87%
“…It should also be mentioned that cyclin D1 is stimulating OR transcriptional activity only when it is free of its regular cdk4/6 partner (Zwijsen et al, 1997), but that free cyclin D1 is more prone to proteolytic degradation than when bound to cdk4/6 (Diehl et al, 1997). Another confounding factor may be the activation by cyclin D1 of p21 (Barbareschi et al, 1997;De Jong et al, 1999). We applied the immunohistological stainings of cell cycle related markers on the residual samples available from the original IKA Tamoxifen study of 1662 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have found amplification of 11q13 chromosomal region (which contains CCND1) in 10 -15% of human primary breast cancers (Ali et al, 1989;Borg et al, 1991;Schuuring et al, 1992;Henry et al, 1993). However, overexpression (at both the mRNA and protein levels) is seen in about 50% of cases, suggesting that mechanisms other than DNA amplification may dysregulate cyclin D1 expression (McIntosh et al, 1995;Gillett et al, 1996;Barbareschi et al, 1997;Jares et al, 1997;Nielsen et al, 1997;Kenny et al, 1999). It is noteworthy that it has been previously described a high correlation between overexpression of CCND1 mRNA and increased presence of Cyclin D1 protein (Bartkova et al, 1994;Gillett et al, 1994).…”
mentioning
confidence: 99%
“…Experimental data show that cyclin D1 expression can be regulated by several factors which may be dysregulated in breast cancer, including growth factors (Musgrove et al, 1993), p53 through p21WAF1 (Chen et al, 1995) and oestrogen (Musgrove et al, 1994;Altucci et al, 1996). It is noteworthy that most CCND1-overexpressing tumours are oestrogen receptor-positive (Hui et al, 1996;Barbareschi et al, 1997;Jares et al, 1997). Finally, cyclin D1 is frequently overexpressed in ductal carcinoma in situ, and also in some benign breast diseases (Weinstat-Saslow et al, 1995;Alle et al, 1998), pointing to a role in the earliest stages of breast tumour development.…”
mentioning
confidence: 99%